Thermochemical calculations of the stability of Ti2AlC in various atmospheres - Stumpf, Martin; Fey, Tobias; Greil, Peter (Journal of Ceramic Science and Technology, 2016)
The thermochemical stability of the MAX phase TiAlC under vacuum, inert Ar, pure O and N and a reactive air atmosphere was explored based on thermochemical equilibrium calculations. Adataset on the enthalpy of formation, standard molar entropy and the temperature variation of the heat capacities of TiAlC and TiC was derived from thermochemical properties given in the literature and implemented in the software package HSC Chemistry. In inert atmosphere TiAlC decomposes peritectically into solid TiC and a liquid Al-rich phase at approximately 1673 °C whereas in vacuum (1 mPa) dissociation into solid TiC and an Al gas phase is observed at a significantly lower temperature of 984 °C. When TiAlC is exposed to air as well as pure O, solid AlO and TiO will form with the carbon being oxidized to gaseous CO and CO. At very low air content, however, the calculations show TiC and AlN as the prevailing reaction products with small fractions of AlO. In a pure nitrogen atmosphere TiAlC is nitrided to AlN, TiN and residual carbon.
Keywords: MAX phase; thermochemical calculations; atmosphere stability